2022
DOI: 10.1530/raf-21-0113
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome and endometriosis

Abstract: The objective of this study was to systematically review the literature on the human microbiome in association with endometriosis. PubMed/Medline, Cochrane, and Embase databases were searched for literature published from 1986 to August 2021. All human studies that assessed the microbiome using 16S rRNA sequencing or by Shotgun Sequence in women with endometriosis were included. Two reviewers independently abstracted data from the selected articles into tables. To assess the quality of included studies, NIH S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Lactobacillus ASV, the most abundant bacteria found in vaginal and endometrium samples, was shared independently of the infertility condition. In contrast, Gardnerella was found in the FRT samples for all patients but shared ASV distributed differently for other conditions associated with infertility while being site-specific for patients with endometriosis [51,57]. One of the most relevant results of this study is the presence of Haemophilus in oral samples from patients with endometriosis.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Lactobacillus ASV, the most abundant bacteria found in vaginal and endometrium samples, was shared independently of the infertility condition. In contrast, Gardnerella was found in the FRT samples for all patients but shared ASV distributed differently for other conditions associated with infertility while being site-specific for patients with endometriosis [51,57]. One of the most relevant results of this study is the presence of Haemophilus in oral samples from patients with endometriosis.…”
Section: Discussionmentioning
confidence: 56%
“…On the contrary, numerous studies linked Lactobacillus to a healthy status [48][49][50]. The microbial profile could change depending on the endometriosis stage, where the early stages preserve the Lactobacillus populations, while the later stages were more diverse [51]. Wessels and Cols.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the complex interplay among bacteria and the host epithelial and immune cells within the female reproductive tract is crucial for preserving the homeostasis of the reproductive system, and that a shift in their equilibrium can potentially contribute to a wide range of conditions 28,53–55 . Even if healthy women may exhibit diverse vaginal microbial compositions, 56 eubiotic vaginal microbiota is normally associated with low bacterial diversity and the dominance of Lactobacillus spp 57 .…”
Section: Discussionmentioning
confidence: 99%
“…28,49 Taxa from the order Rhodospirillales are Furthermore, it has been demonstrated that the complex interplay among bacteria and the host epithelial and immune cells within the female reproductive tract is crucial for preserving the homeostasis of the reproductive system, and that a shift in their equilibrium can potentially contribute to a wide range of conditions. 28,[53][54][55] Even if healthy women may exhibit diverse vaginal microbial compositions, 56 eubiotic vaginal microbiota is normally associated with low bacterial diversity and the dominance of Lactobacillus spp. 57 Despite having been less studied to date, the uterine microbiota in healthy women is characterized by an abundance of genus Lactobacillus, genus Gardnerella and phyla Bacteroidetes, Firmicutes, Proteobacteria, and Actinobacteria.…”
Section: F I G U R E 5 Boxplots Representing Differences In Bray-curt...mentioning
confidence: 99%
“…CA-125 values were used along with the relative abundance of C. disporicum and L. reuteri as a diagnostic tool to differentiate from patients with CPP and no endometriosis, reporting a sensitivity of 89.19% but a specificity of 52.0% [ 27 ]. Other studies have found vaginal L. jensenii to be decreased in patients with CPP-Endo or increased in early-stage endometriosis [ 28 ]. Therefore, further research is needed to conclude the association of vaginal Lactobacillus with the presence, location, and stage of endometriosis and other factors that may confound these studies.…”
Section: Discussionmentioning
confidence: 99%